Random amplified microsatellites (RAMS) analysis ascertains genetic variation of Alternaria alternata causing black spot disease on Carya illinoinensis in South Africa - Achilonu, Conrad Chibunna; Gryzenhout, Marieka; Marais, Gert Johannes; Madisha, M. Thabang; Ghosh, Soumya (Frontiers in Genetics, 2023)
Limited information regarding the occurrence of black spot disease of pecan (Carya illinoinensis), caused by A. alternata, in South Africa is known. The pecan industry is growing rapidly, so it is essential to understand the impact of the fungal pathogen to pecan health. In this study, the genetic variation of 364 A. alternata isolates was investigated by two RAMS primers (CCA5 and CGA5). In total, 6,525 alleles were produced, with a minimum of 3,182 alleles on the CGA5 primer and maximum of 3,343 alleles for CCA5 primer. Further analysis of the primers showed relatively low genetic diversity of A. alternata isolate populations, with mean values; (H = 0.12) and Shannon’s information index (I = 0.20). The analysis of molecular variance (AMOVA) revealed significant differences between populations, with 88% of the genetic variation was found within populations (Nm = 3.59, PhiPT = 0.12), and were not significantly different (p > 0.001). While 12% variation was observed among populations (Nm = 2.89, PhiPT = 0.08) and the estimates were statistically significant (p < 0.001). STRUCTURE HARVESTER output showed that K value is K = 8, where ΔK cannot find the true number of populations because of less variation. The dendrogram cluster tree generated by Ward’s analysis unveiled two main distinct clades and 10 sub-clades, revealing similar findings as those of PCoA analysis clusters. Therefore, it was evident that these analyses depicted no distinct relationship between the A. alternata isolates and their geographic locations or the prevalence of distribution among the populations.